2006
DOI: 10.1001/archinte.166.19.2095
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Mesenteric Artery Stenosis in Elderly Americans

Abstract: Mesenteric artery stenosis was a common finding in free-living elderly patients. At long-term follow-up, the presence of asymptomatic MAS was not associated with death or adverse cardiovascular events. Participants with asymptomatic MAS by duplex ultrasonographic criteria did not experience intestinal infarction or develop chronic intestinal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 25 publications
2
53
0
7
Order By: Relevance
“…A minority of patients with CSD will develop CSS or acute splanchnic syndrome (ASS). A follow-up of the study in elderly subjects in whom duplex had shown CSD, revealed no CSD-related mortality after 6 years of follow-up [13] . This risk is increased in subjects with 2 and 3 vessel CSD.…”
Section: Epidemiologymentioning
confidence: 85%
“…A minority of patients with CSD will develop CSS or acute splanchnic syndrome (ASS). A follow-up of the study in elderly subjects in whom duplex had shown CSD, revealed no CSD-related mortality after 6 years of follow-up [13] . This risk is increased in subjects with 2 and 3 vessel CSD.…”
Section: Epidemiologymentioning
confidence: 85%
“…The index case was initially asymptomatic despite 100% occlusion of the SMA, because of good retrograde filling via the arch of Riolan, which received collaterals from the IMA. There is no randomized trial or clinical guideline for revascularization in such a situation, when there is asymptomatic twovessel involvement [21,25] . With progression of osteal stenosis of the IMA from 50% at baseline to 90% at 15-mo follow-up, the patient became symptomatic with classical postprandial abdominal pain of mesenteric ischemia, for which he underwent successful endovascular mesenteric revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is relatively benign in those with single-vessel disease. In participants of the Cardiovascular Health Study who were found to have isolated coeliac trunk or mesenteric artery disease on duplex ultrasound, there was no increased risk of mortality, intestinal infarction or development of symptoms consistent with CMI over a median follow up period of 6.5years (Wilson et al, 2006). The gold standard of treatment has traditionally been surgical revascularisation in the form of bypass, endarterectomy or embolectomy.…”
Section: Treatment Optionsmentioning
confidence: 99%